2020
DOI: 10.52237/lej.v5i1.152
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English in a virtual classroom using Whatsapp during COVID-19 pandemic

Abstract: Due to the severe situation of Covid-19 pandemic, teacher and students were forced to conduct online learning which was conducted synchronously or virtually. In a virtual classroom, teachers and students are all connected online via communication tools or their devices such as a computer, laptop, or smartphone at the same time. WhatsApp (WA) was considered as an online platform that supported the virtual classroom. Through WA, sharing information combined with some formats of file such as audio, video files, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
0
18
1
2
Order By: Relevance
“…The pandemic and applying social distancing make humans need media to learn and WhatsApp is a good choice. The author's ideas are in line with Asmara (2020) and Sakkir (2016) claimed that the WhatsApp group for language in society course, which was led in the virtual homeroom during the covid-19 pandemic, expected understudies to have extraordinary English abilities, mainly to present the learning materials both spoken and written. As the informing application, this app supports the teachers and students hold the learning and teaching process through a pandemic.…”
Section: Whatsapp As the Media For Learning And Teaching Englishmentioning
confidence: 72%
“…The pandemic and applying social distancing make humans need media to learn and WhatsApp is a good choice. The author's ideas are in line with Asmara (2020) and Sakkir (2016) claimed that the WhatsApp group for language in society course, which was led in the virtual homeroom during the covid-19 pandemic, expected understudies to have extraordinary English abilities, mainly to present the learning materials both spoken and written. As the informing application, this app supports the teachers and students hold the learning and teaching process through a pandemic.…”
Section: Whatsapp As the Media For Learning And Teaching Englishmentioning
confidence: 72%
“…Carrillo and Flores (2020) also discussed the presence of some students in their homes who did not have computer-internet access and found that there was a decline in their education. The problems with internet connectivity have been highlighted several times by researchers regarding the hardware (Asmara, 2020;Dias, Lopes & Teles, 2020). Dutta and Smita (2020) expressed that the Covid-19 pandemic process found that students experience problems such as lack of electronic devices, limited internet access, expensive internet fee, slow internet speed and difficulties using online platforms in their studies with university students in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Uzaktan eğitimde başarı isteniyor ise teknolojik imkanların iyileştirilip geliştirilmesi önemlidir (Rose ve Blomeyer, 2005). Ayrıca alan yazında, internet bağlantısı sorunu birçok defa vurgulanmıştır (Asmara, 2020;Mohan, vd., 2020;Dias, Lopez ve Teles, 2020). Evinde teknolojik araç olmayan ya da internet altyapısı zayıf olan öğrenciler uzaktan eğitimden faydalanamamakta dolayısıyla da dezavantajlı duruma düşmektedir.…”
Section: Tablo 2 Uzaktan Eğitim Sürecinde Karşılaşılan Sorunlar Temasıunclassified